The prognosis of subjects showing a reduced estimated glomerular filtration rate without albuminuria in Japanese patients with type 2 diabetes: a cohort study for diabetic kidney disease - Ito, Hiroyuki; Antoku, Shinichi; Izutsu, Takuma; Kusano, Eiji; Matsumoto, Suzuko; Yamasaki, Tomoko; Mori, Toshiko; Togane, Michiko (Clinical and experimental nephrology, 2020)
Background To determine the renal and cardiovascular prognosis and all-cause mortality of Japanese patients with type 2 diabetes showing a reduced estimated glomerular filtration rate (eGFR) without albuminuria. Methods A population of 675 patients with type 2 diabetes was prospectively observed for 4 years to determine the renal and cardiovascular outcomes and mortality. The subjects were divided into the four groups: those with a preserved eGFR and no albuminuria ( n = 306), a preserved eGFR and albuminuria ( n = 151), a reduced eGFR and no albuminuria ( n = 96), and a reduced eGFR and albuminuria ( n = 122). The Cox proportional hazard model and Fine and Gray method were used to assess between-group differences in the risk of mortality and cardiovascular events. Results In the group with a reduced eGFR, the eGFR value did not significantly change in the subjects without albuminuria (0 ± 8 mL/min/1.73 m 2 ), whereas it decreased continuously in those with albuminuria (-6 ± 12 mL/min/1.73 m 2 ). The incidence of cardiovascular events was significantly ( P = 0.03) higher in the subjects with albuminuria (17%) than those without albuminuria (7%) in the group with a reduced eGFR. Cardiovascular events were significantly ( P < 0.01) more frequent in the group with a reduced eGFR than in those with a preserved eGFR in both subjects with and without albuminuria. Conclusions The risk of end-stage kidney disease in non-albuminuric subjects with a reduced eGFR is considered to be low. We should focus on cardiovascular prognosis, because these patients are still at high risk of cardiovascular events, even though the prognosis is better in comparison to albuminuric patients.